The mermaid and Mrs. Hancock - Gowar, Imogen Hermes (New York, N.Y. : Harper, an imprint of HarperCollinsPublishers, 2018)
When one of his trading vessels returns to eighteenth-century London with the remarkable body of a mermaid, Jonah gains entry into high society and falls in love with a highly accomplished courtesan, with unexpected consequences.
Keywords: Seafaring life -- Fiction; Mermaids -- Fiction; Man-woman relationships -- Fiction; Voyages and travels -- Fiction; Seafaring life -- Fiction; Mermaids and mermen -- Fiction; Man-woman relationship -- Fiction; Voyages and travels -- Fiction; Historical fiction; Humorous fiction; Historical fiction